Characterisation of 30 microsatellite loci for the Tehuelche scallop, Aequipecten tehuelchus (d'Orbigny, 1842) and their use for estimating demographic parameters relevant to fisheries management. (3rd July 2018) - Domínguez-Contreras, José Francisco; Munguía-Vega, Adrián; Getino-Mamet, Leandro Nicolás; Soria, Gaspar; Parma, Ana
ABSTRACT: Aequipecten techuelchus is an endemic scallop of the Argentine biogeographic province in the southwest Atlantic Ocean which supports a commercial fishery that has presented strong fluctuations since the 1960s. It is unclear if distinct localities constitute a single panmictic population. We used next-generation sequencing to obtain microsatellite loci that could be used to evaluate genetic diversity and differentiation among populations. We developed 30 polymorphic microsatellite loci, of which 13 meet the standard criteria required for population genetic analyses, including Hardy-Weinberg equilibrium, not being linked and with a low frequency of null alleles. The described microsatellite loci were used to estimate relatedness and effective population size, and to test for recent and historic population bottlenecks. Our results suggest that the population of the Tehuelche scallop from San Román, Gulf of San José, Patagonia shows a relatively large effective population size, high levels of genetic polymorphism, low levels of inbreeding and no signs of recent or historic drastic population reductions. These preliminary results should be confirmed with larger sample sizes and the inclusion of other nearby populations.